Lower back pain amongst medical trainees in clinical rotations: implications for choosing future career regarding medical practice - Hakiranuye, Samuel; Kiwanuka, Frank; Asiimwe, Daniel; Posti, Jussi P.; Lule, Herman (Frontiers in Public Health, 2024)
BackgroundLow back pain (LBP) is an increasing concern amongst medical students. There is a dearth of publications regarding how the occurrence of LBP impact medical trainees’ career decisions.ObjectiveTo determine: (i) the point and annual prevalence of LBP amongst Ugandan medical students, (ii) its associated factors, and (iii) whether the experience of LBP during clinical rotations influence medical students’ career choices regarding medical practice.MethodsA multi-center cross-sectional study of 387 randomly selected clinical-phase students was conducted in three Ugandan medical schools, during 17th January to 10th March 2023. Proportions of participants with current and 12-months history of LBP were computed as well as odds for career prospects. We performed binary logistic regression models to determine factors associated with LBP at 95% confidence interval regarding p < 0.05 as statistically significant.ResultsThe response rate was 100%. Participants’ mean age was 24.7 ± 3.2 years of which 66.2% (256/387) were males. The point and annual prevalence of LBP was 52.5% (203/387) and 66.1% (256/387) respectively. Age [OR 1.23, 95% CI (1.03–1.47), p = 0.02], time spent sitting per day [OR 1.08, 95% CI (1.06–1.3), p < 0.01], perceived influence of LBP on future medical career [OR 4.75, 95% CI (1.87–12.06), p < 0.01] were the significant predictors of LBP. LBP interrupted the students’ learning for at least 6.8 ± 12.8 h in 42.4% of participants. Nearly half of participants affirmed that their LBP experience would influence their career prospects. Based on their LBP experiences, trainees ruled out surgery 51.5% (172/334), obstetrics/gynecology 29.6% (99/334), paediatrics 18.3% (61/334), and internal medicine 17.7% (59/334) as their future career specialties. The proportion of trainees that would not consider surgical as opposed to medical disciplines were 81.1% vs. 36.0%, respectively, (p < 0.001).ConclusionThe high prevalence of low back pain among medical students impacts their choices of future medical career with an aversion towards specialization in surgical disciplines. This has far-reaching implications on the disparities in specialist physician health workforce in Low-middle-income countries.